Hedonism as Reflected in Hemingwayâs `The Snows of Kilimanjaro` - Setyaningrum, Vincentia Gita Yulis; Samanik, Samanik (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This research deals with the hedoism in The Snows of Kilimanjaro short story by Ernest Hemingway. The writers use hedoism as the main theory to analyze because the problems of this short story are related to luxurious lifestyle and temporary happiness. The objectives are to find the hedoism values and the influence of hedoism from the main character of the short story, which the writer wants to convey to the reader. The study was conducted by applying qualitative research. Data that uses this study are primary data were reached from The Snows of Kilimajaro short story. Then, secondary data were reached from literature review and other sources information that related to object of this research. The technique for collecting the data was documentary technique. After analyzing the short story, it was found one of hedoism value which is materialism. The influence of hedoism can be seen by the main character Harry descriptions with the the cases of a narration and dialogues, the writer concludes some influence of hedoism that have a bad behaviour and personalities to the readers which is alchoholics drinks becomes a part of lifetyle. The other reason hedoism portrayed by the main character are found from their own surroundings such as social condition or environments even it cames from themselves.